Media Literacy as an Inquiry-Based Framework for Exploring Desocialization - Iris Metzgen-Ohlswager (Adult Education Research Conference, 2010)
Our educational landscape is dramatically changing; youth and adults have access to more information than ever before in history. As a world we have embraced technology with open arms, but rarely have reflected on its implications or actively educated people on how to deconstruct the endless stream of messages. Media literacy or the ability to access, analyze, evaluate, and create media, and can be used as an inquiry-based framework for exploring desocialization in the classroom, community, or workplace.